Pengaruh Variasi Komposisi Graphite dan Arang Tempurung Kelapa Pada Baterai Lithium-Ion Terhadap Konduktivitas Listrik, Kekuatan Bending dan Mikrostruktur - Rendika, Fauzi; Dedikarni , Dedikarni (Journal of Comprehensive Science, 2025)
The development of electric vehicle technology drives research on more efficient and environmentally friendly lithium-ion battery anode materials. This study aims to analyze the effect of composition variations of graphite and coconut shell charcoal on electrical conductivity, bending strength, and microstructure of polymer conductor plates for lithium-ion battery applications. The method used was the manufacture of conductor plates with graphite:coconut shell charcoal:epoxy resin compositions of 70%:20%:10%, 60%:30%:10%, and 50%:40%:10% using dry pressing technique with 5 Tons pressure. Testing was conducted following ASTM B193 standard for electrical conductivity, ASTM D790 for bending strength, and microstructure analysis using Olympus BX53M microscope. The results showed that samples with graphite 70%:coconut shell charcoal 20%:epoxy resin 10% composition produced the highest electrical conductivity of 187.8 S/cm and lowest resistivity of 0.071 ?. Conversely, samples with graphite 50%:coconut shell charcoal 40%:epoxy resin 10% composition produced the highest bending strength of 3.84 MPa. Microstructure analysis showed that increasing coconut shell charcoal composition reduced material porosity and increased mechanical strength. This research proves that higher graphite composition increases electrical conductivity, while higher coconut shell charcoal composition increases bending strength but decreases electrical conductivity.